Analisis Strategi Pemasaran dengan Menggunakan Metode SWOT Guna Peningkatan Penjualan Produk Lemari di UD Abdi Rakyat - Muhammad Rizky Surya Aistiawan; Deny Andesta (Jurnal Serambi Engineering, 2022)
UD Abdi Rakyat is a business engaged in the manufacture of cabinet products with the ingredients are glass and aluminum. In the process of selling products often experience conditions where the number of cabinet sales is volatile and erratic every week, characterized by an increase and decrease in unstable sales. This research uses SWOT analysis that contains strategy planning steps to evaluate all forms of strengths, weaknesses, opportunities and threats in an effort. The purpose this study to find the factors that cause fluctuating sales and know the marketing strategies to be used in efforts to increase sales of their products. The results of this study show that there are various internal-external factors that hinder the course of the business. The total score value of the IFASEFAS matrix calculations is Strength 2.86, Weakness 2.33, Opportunity 1.80 and Threat 1.70. The results the SWOT matrix diagram show that UD. Abdi Rakyat is in quadrant I and has a positive weighted difference value (0.53;0.10). From the various kinds of formation strategies to increase sales of cabinet products, it was concluded that the business needed to apply the SO strategy so that the company's goals could be achieved quickly and appropriately.